Gambling-related attitudes and dimensional structure of the GABS-15 in outpatient addiction care patients: associations with gambling disorder - Bickl, Andreas M.; Loy, Johanna K.; Kraus, Ludwig; Grüne, Bettina; Hoch, Eva; Schwarzkopf, Larissa (Frontiers in Psychiatry, 2024)
Individuals with gambling disorder (GD) harbor cognitive distortions and dysfunctional beliefs about gambling that may foster problematic gambling behaviour. Evidence on particularly detrimental attitudes and beliefs is however lacking. To close this knowledge gap, we analysed associations between gambling attitudes and beliefs (Gambling Attitudes and Beliefs Survey (GABS-15)) and severity of gambling disorder (DSM-5 criteria met) in a German cohort of 123 individuals receiving outpatient gambling treatment. Data from the "Katamnese-Study" covering a 36-months timeframe with 5 assessment points was pooled. The multidimensional structure of the GABS-15 was examined using explorative and confirmatory factor analyses, followed by mixed-effect regression models using different operationalizations of the GABS-15. A threefactorial structure comprising "attitudes while gambling", "sensation-seeking / excitement", and "gambling fallacies" demonstrated better fit indices than the GABS-15 sum score. Only the "gambling fallacies " factor (1.00, p<0.05; 15.36, p < 0.01) was significantly associated with increased severity of GD. As a one-dimensional conceptualization of gambling-related attitudes and beliefs might not sufficiently guide staff of outpatient treatment facilities regarding priority setting in gambling care, evidence on attitudes with particularly detrimental associations is highly warranted. Here, focussing on mitigating "gambling' fallacies" by tailored treatment strategies appears promising.